Pengaruh Layanan Konseling Kelompok Dengan Teknik Restrukturisasi Kognitif Terhadap Kecemasan Berbicara di Depan Umum Pada Siswa Kelas VIII SMP Negeri 17 Kota Bengkulu - Dita Aprianti; Sri Saparahayuningsih; Anni Suprapti (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2024)
This study aimed to describe the effect of group counseling services with cognitive restructuring techniques on students' public speaking anxiety. This research used experimental method with one-group pretest-posttest design. The sample of this study amounted to 6 students who were taken by purposive sampling technique with data collection using a public speaking anxiety questionnaire. Data were analyzed using t-test (paired sample t-test). The t-test results show the value of t = 20.208 (p <0.05). This means that there was a significant effect of group counseling services with cognitive restructuring techniques on reducing students' public speaking anxiety levels. Based on the results of this study, it is recommended to guidance and counseling teachers to use group counseling services with cognitive restructuring techniques to reduce public speaking anxiety in students. Keywords: group counseling, cognitive restructuring, speaking anxiety